Postmortem Study of Cause of Death Among Children Hospitalized With Respiratory Illness in Kenya. Issue 8 (4th May 2021) - Njuguna, Henry N.; Zaki, Sherif R.; Roberts, Drucilla J.; Rogena, Emily A.; Walong, Edwin; Fligner, Corinne L.; Keating, M. Kelly; Gachii, Andrew K.; Maleche-Obimbo, Elizabeth; Irimu, Grace; Mathaiya, John; Orata, Noelle; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: In resource-limited settings, acute respiratory infections continue to be the leading cause of death in young children. We conducted postmortem investigations in children <5 years hospitalized with a clinical diagnosis of respiratory disease at Kenya's largest referral hospital. Methods: We collected respiratory and other tissues postmortem to examine pathologic processes using histology, molecular and immunohistochemistry assays. Nasopharyngeal, trachea, bronchi and lung specimens were tested using 21-target respiratory pathogen real-time reverse transcription polymerase chain reaction assays deployed on Taqman Array Cards. Expert panels reviewed all findings to determine causes of death and associated pathogens. Results: From 2014 to 2015, we investigated 64 pediatric deaths (median age 7 months). Pneumonia was determined as cause of death in 70% (42/52) of cases where death was associated with an infectious disease process. The main etiologies of pneumonia deaths were respiratory syncytial virus (RSV) (n = 7, 19%), Pneumocystis jirovecii (n = 7, 19%), influenza A (n = 5, 14%) and Streptococcus pneumoniae (n = 5, 14%)—10% of cases had multi-pathogen involvement. Among the other 10 deaths associated with a nonpneumonia infectious process, 4 did not have an etiology assigned, the others were associated with miliary tuberculosis (2), cerebral thrombosis due to HIV (1), Enterobacteriaceae (1), rotavirus (1), and 1 case of respiratory infection with severe hypokalemia associated with RSV. Conclusions: In spite of well-established vaccination programs in Kenya, some deaths were still vaccine preventable. Accelerated development of RSV monoclonal antibodies and vaccines, introduction of seasonal influenza vaccination, and maintenance or improved uptake of existing vaccines can contribute to further reductions in childhood mortality.